\((-2)^4 - 2^4 + (-3)^3 - 3^3\)

I was wondering how to attack this problem

SoggyPerson May 3, 2020

#1**+1 **

Ok here's my solution,

\(\begin{align*} (-2)^4 &= (-2)(-2)(-2)(-2) = 16,\\ 2^4 &= 2\cdot 2\cdot 2\cdot 2 = 16,\\ (-3)^3&= (-3)(-3)(-3) = (9)(-3) = -27,\\ 3^3 &= 3\cdot3\cdot3 = 27, \end{align*}\)

\((-2)^4 -2^4 + (-3)^3 - 3^3 = 16-16 -27-27 = \boxed{-54}.]\)

So the thing to take away in this question is to always remember that in solving these questions **the order of operations in KEY!!!**

LuckyDucky May 3, 2020

#1**+1 **

Best Answer

Ok here's my solution,

\(\begin{align*} (-2)^4 &= (-2)(-2)(-2)(-2) = 16,\\ 2^4 &= 2\cdot 2\cdot 2\cdot 2 = 16,\\ (-3)^3&= (-3)(-3)(-3) = (9)(-3) = -27,\\ 3^3 &= 3\cdot3\cdot3 = 27, \end{align*}\)

\((-2)^4 -2^4 + (-3)^3 - 3^3 = 16-16 -27-27 = \boxed{-54}.]\)

So the thing to take away in this question is to always remember that in solving these questions **the order of operations in KEY!!!**

LuckyDucky May 3, 2020

#3

#5**+2 **

This image is excellent I recommend to view it!

https://www.google.com/url?sa=i&url=https%3A%2F%2Fwww.onlinemath4all.com%2Fgemdas-order-of-operations.html&psig=AOvVaw3v8y-v4md6S_WjSpIc2j7Q&ust=1588636312946000&source=images&cd=vfe&ved=0CAIQjRxqFwoTCODHq8vxmOkCFQAAAAAdAAAAABAD

LuckyDucky
May 3, 2020